Synthesis of Zn(II) and Co(II) Complexes with a Schiff Base Derived from Malonic Acid Dihydrazide for Photo-Stabilizers of Polystyrene - Rehab Ghalib Hammoda; Naser Shaalan (Universitas Gadjah Mada, 2023)
In this study, novel Schiff base complexes with Zn(II) and Co(II) ions were successfully synthesized. The malonic acid dihydrazide was converted into the Schiff base ligand by combining it with 1-hydroxy-2-naphthaldehyde, and the last step required reacting it with the appropriate metal(II) chloride to produce pure target complexes. The generated complexes were thoroughly characterized using FTIR, 1H-NMR, 13C-NMR, GC-mass, and UV-Vis spectroscopies. In order to photo-stabilize polystyrene (PS) and reduce the photodegradation of its polymeric chains, these chemicals have been used in this work. The efficiency of the generated complexes as photo-stabilizers was evaluated using a variety of techniques, including FTIR, weight loss, viscosity average molecular weight, light and atomic force microscopy, scanning electron microscopy (SEM), and energy dispersive X-ray (EDX) mapping. These tests corroborated each other and demonstrated how effectively new compounds stabilize PS photographs. As a result, compared to blank PS, they reduce the photodegradation of PS films containing these complexes after 300 h of exposure to UV radiation with a wavelength of 313 nm. Also, it has demonstrated how effective the cobalt complex is as a photo-stabilizer. The highly conjugated systems in these chemicals are to blame for this.